The contrasting reactivity of trans - vs. cis -azobenzenes (ArNNAr) with benzynes - Sneddon, Dorian S.; Hoye, Thomas R. (Chemical science (Cambridge), 2023)
We report here a study that has revealed two distinct modes of reactivity of azobenzene derivatives (ArNNAr) with benzynes, depending on whether the aryne reacts with a trans - or a cis -azobenzene geometric isomer. Under thermal conditions, trans -azobenzenes engage benzyne via an initial [2 + 2] trapping event, a process analogous to known reactions of benzynes with diarylimines (ArCNAr). This is followed by an electrocyclic ring opening/closing sequence to furnish dihydrophenazine derivatives, subjects of contemporary interest in other fields ( e.g. , electronic and photonic materials). In contrast, when the benzyne is attacked by a cis -azobenzene, formation of aminocarbazole derivatives occurs via an alternative, net (3 + 2) pathway. We have explored these complementary orthogonal processes both experimentally and computationally.